Migrating to a shared Library Management System: evaluation from the perspective of librarians and lessons learned. Issue 6 (3rd May 2021) - Kouis, Dimitrios; Kyprianos, Konstantinos; Efthymiou, Foteini; Koulouris, Alexandros; Karabela, Antonia
Abstract : Purpose: The purpose of this article is to investigate certain aspects, problems and benefits from the migration to a shared Library Management System (LMS). Design/methodology/approach: A review of the literature and a quantitative survey was conducted, based on a structured questionnaire, with a response rate of 44.7%. Findings: Among the crucial issues that should be taken seriously into consideration when transiting into a new and shared LMS, are the audit of the data quality before migration, the employees' training design and the composition of the LMS central support team. The benefits of a shared LMS are mainly effectiveness in terms of libraries' budgets and time for the employees' day-to-day work. Originality/value: The survey presented in this article evaluates the merits of a shared LMS and contributes innovative aspects to the existing bibliography by investigating issues and problems that arose during the transition. This way, the professionals involved in similar initiatives will benefit by avoiding possible mistakes and drawbacks when implementing such a project.